ANALISIS MANAJEMEN WAKTU MAHASISWA JURUSAN MANAJEMEN BISNIS SYARIAH PEKERJA PART TIME UNIVERSITAS ISLAM NEGERI RADEN MAS SAID SURAKARTA - Setyawan, Muhammad Arditya; Hapsari, Ryana Nimas; Romadhoni, Nisa Sholikhah (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
This research aims to find out how students who work part time manage their time. This research uses a descriptive-qualitative method that focuses problems on the basis of facts. The subjects of this research were students at the Raden Mas Said State Islamic University, Surakarta, semester 1 of the Sharia Business Management study program. The data collection technique is structured interviews. Data analysis used interactive modeling techniques. The results of this research show that students work part time at night, on holidays, and in their free time when there are no lecture hours. Time effectiveness is done to balance study and work hours.